THE UNDERSTANDING CHILDREN AS BULLIES FROM A CRIMINOLOGICAL PERSPECTIVE - Sulastri, Lusia (UNISSULA, 2024)
The phenomenon of violence in Indonesia does not only occur among high school and middle school teenage students; even at the elementary school level, the phenomenon of bullying occurs. This research is aimed at finding out the causes of child bullying from a criminological perspective and overcoming bullying crimes committed by children at school. In fulfilling the research objectives, this research uses normative juridical methods. The research results show that the causes of child bullying from a criminological perspective consist of internal factors, namely children's egocentrism, revenge, parents who often punish their children excessively, stressful home situations, aggression, and hostility. Apart from that, external factors include discriminatory behavior among both teachers and students, a lack of supervision and ethical guidance from teachers, a large gap between rich and poor students, and very rigid discipline patterns. Dealing with bullying crimes committed by children at school must be given special treatment aimed at forming good attitudes and behavior in a penal manner by paying attention to the best interests of the child and a non-penal approach.